Особенности образа современного русского интеллигента на примере романа Алексея Варламова Затонувший ковчег (1997) - Królikiewicz, Natalia (Studia Rossica Posnaniensia, 2020)
The article focuses on the image of the modern Russian intellectual, depicted in the artistic text of Aleksey Varlamov, the Sunken Ark. Understanding the phenomenon of the Russian intelligentsia in the analysed literary work is associated with the problem of the opposition of reason and faith in the process of the personality formation of the modern intellectual. The analysis carried out in the text allows not only to trace and better understand the social processes of the crisis period in Russia, but also to notice their enormous impact on the consciousness of the main hero-intellectual Ilya Petrovich. The use of the methodology of historical and literary research in the work is adequate to the problems posed. The novel under analysis, as a kind of warning, has a deep philosophical undertone that touches upon the problems of faith, unbelief, freedom of the individual and the pursuit of moral perfection. Varlamov’s intellectual, as a typical “hero of our time”, regardless of his weakness, defenselessness and internal rupture, seems to be most needed in life.